Pengaruh Cita Rasa, Kualitas Produk Dan Pelayanan Terhadap Kepuasan Pelanggan Seblak Radja Sidodadi Sidoarjo - Widya Inayatul Umah; Iswati Iswati (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2023)
This research was conducted in order to determine the effect of taste (X1) product quality (X2) service quality (X3) on customer satisfaction (Y), in seblak radja. This study uses quantitative research methods with a sample of 100 respondents. The population of respondents are consumers of seblak radja in Sidoarjo. In analyzing the data used validation test, reliability test, t test, f test and coefficient of determination test. The results of this study show that taste, product quality and service quality simultaneously affect customer satisfaction. This means that the better the taste, product quality and service will further increase customer satisfaction at Seblak Radja Sidodadi Sidoarjo.